Treatment of Schizophrenia and Comorbid Substance Use Disorder - Green, A.I.; Salomon, M.S.; Brenner, M.J.; Rawlins, K. (Current Drug Targets-CNS & Neurological Disorders, 2002)
Comorbid alcohol and substance use disorders occur commonly among patients with schizophrenia and contribute to the morbidity of schizophrenia. These comorbid disorders add greatly to the financial costs and emotional toll that schizophrenia places on patients, families and the entire mental health system. While the basis for the increased abuse of alcohol and other substances in patients with schizophrenia have been linked by some investigators to ”self-medication“ of negative symptoms of schizophrenia or extrapyramidal system effects of typical antipsychotics, we have presented a neurobiologic formulation suggesting that alcohol or other substances may transiently correct a dysfunction of the dopamine-mediated mesocorticolimbic pathways in patients with schizophrenia - pathways linked to brain reward circuits. This formulation further suggests that alcohol or other substances serve to transiently enhance the functioning of this circuit by improving the ”signal detection“ capability of the dopamine-rich mesocorticolimbic pathways. Treatment of comorbid substance use disorder in patients with schizophrenia involves careful use of psychosocial approaches aimed at fostering program participation and at enhancing the likelihood of abstinence. While the typical antipsychotics do not limit the comorbid substance use, and may actually worsen it, preliminary data suggest the novel antipsychotic clozapine may have the unusual ability to dramatically decrease alcohol and other substance use in patients with schizophrenia. It is not clear whether other novel antipsychotics share this ability of clozapine to limit alcohol and substance abuse. We have proposed that the effect of clozapine in this population may relate to its broad pharmacological effects, including its relatively weak blockade of the dopamine D2 receptor and its potent blockade of the serotonergic 5-HT2 receptor and the noradrenergic alpha 1 and alpha 2 receptors. Studies of other agents, employed in the pharmacotherapy of alcohol and substance use disorders without schizophrenia, are currently underway in patients with schizophrenia and comorbid disorders.
Keywords: naltrexone